KOMBINASI UJI LARVASIDA EKSTRAK DAUN BELUNTAS (Pluchea indica linn) DAN BAWANG PUTIH (Allium Sativum) DALAM MEMBUNUH LARVA Aedes aegypti: COMBINATION OF LARVACIDE TEST OF BELUNTAS LEAF EXTRACT (Pluchea indica linn) AND GARLIC (Allium Sativum) IN KILLING Aedes aegypti LARVAE - Hariyanti, Firda Natasya; Chamid, Abdul; Prasetya, Indra Adi Wira; Suryani, Elsa Mega; Pradana, Muhammad Sungging (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2024)
Aedes aegypti is a type of mosquito that causes dengeu hemorrhagic fever as the main carrier (primary vector) of dengeu virus. This disease is very common in Indonesia, efforts to eradicate mosquito larvae are relatively cheap, simple by means of public health counseling and eradication of mosquito nests using insecticides. The purpose of this study was to determine the effectiveness of the combination of beluntas leaf extract (Pluchea indica linn) and garlic (Allium satisum) in killing Aedes aegypti mosquito larvae at concentrations of 10%, 20%, 50%, and 100% for 24 hours. This type of study used experimental research with a research sample of 400 Aedes aegypti mosquito larvae. The results showed that the combination of beluntas leaf extract (Pluche indica linn) and garlic (Allium satisum) has effectiveness as a larvicide of Aedes aegypti instar III. The effective concentration on the combination of beluntas leaf extract (Pluchea indica linn) and garlic (Allium sativum) is 50% within 24 hours.